Fragmentation considered harmful. - Kent, C.A.
Internetworks can be built from many different kinds of networks, with varying limits on maximum packet size. Throughput is usually maximized when the largest possible packet is sent; unfortunately, some routes can carry only very small packets. The IP protocol allows a gateway to fragment a packet if it is too large to be transmitted. Fragmentation is at best a necessary evil; it can lead to poor performance or complete communication failure. There are a variety of ways to reduce the likelihood of fragmentation; some can be incorporated into existing IP implementations without changes in protocol specifications. Others require new protocols, or modifications to existing protocols.
Keywords: Computer systems organization; Computer communication networks; Design; Performance; Standardization